(untitled) (Bangladesh Armed Forces Medical Journal, 2026)
Objective: To determine the association between severity of cholecystitis and gallstone size. Study Design: Cross-sectional study. Place and Duration of Study: Department of Surgery, Combined Military Hospital, Rawalpindi, from 22nd August 2024 to 21st September 2024. Methodology: This study utilized a cross-sectional design to explore the relation between severity of cholecystitis as assessed by the Parkland grading system and gallstone size, following Ethics Review Board approval. The sample included 67 respondents diagnosed with cholecystitis who underwent laparoscopic cholecystectomy during the study period after obtaining written consent. Data on Parkland grading scores and gallstone size were collected. Gallstone diameter was measured using vernier callipers, while patients’ severity of cholecystitis during surgical intervention was labelled as per Parkland grading. Gallstone size served as the dependent variable, and Parkland grading was the independent variable. Results: Study show that there is a statistically significant association between the severity of cholecystitis and gallstone size (p < 0.001). This suggests that more severe grades of cholecystitis were associated with larger gallstone sizes. Conclusion: A significant relationship was observed between the Parkland Grading Score and Gallstone size. Bangladesh Armed Forces Med J Vol 58 No (2) December 2025, pp 21-8